Reference intervals for hemoglobin and mean corpuscular volume in an ethnically diverse community sample of Canadian children 2 to 36 months - Jemila S. Hamid; Eshetu G. Atenafu; Cornelia M. Borkhoff; Catherine S. Birken; Jonathon L. Maguire; Mary Kathryn Bohn; Khosrow Adeli; Mohamed Abdelhaleem; Patricia C. Parkin (BMC, 2021)
Abstract Objective To establish reference intervals for hemoglobin and mean corpuscular volume (MCV) in an ethnically diverse community sample of Canadian children 36 months and younger. Methods We collected blood samples from young children at scheduled primary care health supervision visits at 2 weeks, 2, 4, 6, 9, 12, 15, 18, 24, and 36 months of age. Samples were analyzed on the Sysmex XN-9000 Hematology Analyzer. We followed the Clinical and Laboratory Standards Institute guidelines in our analysis. Data were partitioned by sex and also combined. We considered large age partitions (3 and 6 months) as well as monthly partitions. Reference intervals (lower and upper limits) and 90% confidence intervals were calculated. Results Data from 2106 children were included. The age range was 2 weeks to 36 months, 46% were female, 48% were European and 23% were of mixed ethnicity. For hemoglobin, from 2 to 36 months of age, we found a wide reference interval and the 90% confidence intervals indicated little difference across age groups or according to sex. For MCV, from 2 to 7 months of age there was considerable decrease in the reference interval, which was lowest during the second year of life, followed by a slight increase in the last months of the third year of life. Conclusion These findings suggest adoption of a single hemoglobin reference interval for children 2-36 months of age. Further studies in children under 4 months of age are needed. Trial registration TARGet Kids! cohort is registered at ClinicalTrials.gov. www.clinicaltrials.gov . Identifier: NCT01869530 .